STATUS AND PROSPECTS OF IMPLEMENTING REPORTING IN THE AGRICULTURAL SECTOR AS AN INFORMATION BASE FOR DECISION-MAKING IN THE FIELD OF TAXATION - IVANENKO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the current status and prospects of implementing integrated reporting in the agricultural sector of Ukraine as a source of information for making management decisions, in particular in the field of taxation. The growing interest of investors in non-financial aspects of enterprises’ activities necessitates the improvement of traditional forms of reporting. Considering global trends, integrated reporting is becoming a relevant tool for ensuring transparency for agricultural enterprises, which covers economic, environmental, social and managerial components. The article examines approaches to disclosing information in the annual reports of leading Ukrainian agricultural enterprises, in particular MHP, Kernel, Astarta, etc. It was concluded that very limited number of companies provide the appropriate level of publicity and sufficiency of information in their annual reports, while most enterprises disclose only financial reports, or provide their accounts only upon request to a limited number of stakeholders. The informativeness and readability of annual reports were assessed as key characteristics of their effectiveness, in particular in the context of administering taxes. The article emphasizes the potential of integrated reporting as a tool suitable not only for corporate governance, but also for reducing the risks of tax evasion and increasing the fiscal transparency of agricultural business. The feasibility of legislative stimulation of the implementation of integrated reporting in Ukraine was substantiated using the experience of EU member states, where such practice is mandatory for public interest entities. Directions for further research were proposed, in particular in developing reporting indicators which should provide for the industry specifics such as seasonality, biological transformation of assets and social guidelines for the development of rural areas.